Pengaruh Online Customer Rating Dan Online Customer Review Terhadap Keputusan Pembelian Produk Makanan Pada Bakoel Camilan Melalui Gofood - Ananda, Dea; Andriani, Nurita (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
The purpose of this study was to determine the effect of online customer ratings and online customer reviews on purchasing decisions for food products at Bakoel Snacks through GoFood for Bakoel Camilan Instagram followers. This research was conducted using a quantitative descriptive method. Sampling of this study used purposive sampling with a total of 70 respondents, using multiple linear regression analysis techniques. The results of the study on the online customer rating variable (X1) show that the tcount is 4.910 ttable 1.667 with a significance level of 0.000 0.05. The online customer review variable (X2) shows that the tcount is 3.257 ttable 1.667 with a significance level of 0.002 0.05. The results of the F test show that the value of Fcount is 23.131 Ftable 3.13 with a significance level of 0.000 0.05. Thus, the conclusions of this study are a) Online customer ratings have a positive and significant effect on the decision to purchase food products at Bakoel Camilan through GoFood, b) Online customer reviews have a positive and significant effect on purchasing decisions for food products at Bakoel Camilan through GoFood, c) Online customer rating and online customer review together have a positive and significant effect on the variable of the decision to purchase food products at Bakoel Camilan through GoFood.